Preditores da restrição na participação pós-acidente vascular encefálico - Iza de Faria (2016)
Stroke is the main cause of disability in Brazil and has significant economic and social impacts. The restriction in participation is a significant consequence for individuals with stroke, being associated with poor perceptions of quality of life, health status, and well-being. Therefore, participation is a central concept during the recovery process of functionality after stroke. According to the International classification of functioning, disability, and health (ICF) framework, participation is theresult of the interaction between factors related to the health condition, body functions/structure, activity, and/or contextual factors. Therefore, to better comprehend the factors related to restrictions in participation, it is necessary to analyse the contributions of the components of functionality, concomitantly considering the influence of the impairments, activity limitations, and environmental factors. Therefore, the purpose of this study was to investigate which variables, which are commonly focused during rehabilitation interventions and listed in the components of body functions and structure, activity, and environmental factors, would best predict participation after stroke. Participated 109 subjects, who had amean age of 58±12 years and a mean time since the onset of the stroke of 64±64 months. The variables related to the component of body functions and structure included muscular strength (handgrip strength and global isometric strength of the LE muscles); motor coordination of both the UE (finger-to-nose test) and LE (Lower Extremity Motor Coordination Test - LEMOCOT), and depressive symptoms(Geriatric Depression Scale - GDS). The activity component was assessed by measures of both capacity (Test d'Évaluation des Membres Superieurs of Personnes âgées - TEMPA and 10-meter walking test) and performance (ABILHAND-Brazil and ABILOCO-Brazil). The component related to the environmental factors was evaluated by the Measure of the Quality of the Environment - MQE-Brazil. Finally, restriction in participation was measured by the Brazilian version of the Assesment of Life Habits3.1 (LIFE-H 3.1- Brazil). Two models were created for the multiple linear regression analyses, one for the sub-scale of daily activities and another for the sub-scale of social roles of the LIFE-H 3.1-Brazil. The forward method for the selection of variables was chosen to identify, from the group of the selected independent variables, those that significantly explained participation, i.e., the LIFE-H 3.1-Brazil scores, as well as to determine the explanatory power of the predictive models. For the daily activity model, locomotion ability (ABILOCO-Brazil scores) explained 39%(F=66.5; p<0.0001) of the variance of the LIFE-H 3.1-Brazil scores. When manual ability (ABILHAND-Brazil scores) were included in the model, the explained variance increased to 49% (F=50.5; p<0.0001). By adding the GDS scores and walking speed, the explained variance increased to 54% (F=10.2; p=0.002) and 59% (F=15.1; p<0.001), respectively. For the social role model, walking speed explained 32% (F=47.8; p<0.0001) of the variance of the LIFE-H 3.1-Brazil scores. When depressive symptoms (GDS scores) were included in the model, the explained varianceincreased to 42% (F=11.4; p<0.0001). By adding UE function (TEMPA), the explained variance increased to 49% (F=12.9; p=0.001). The results showed that the activity-related measures had higher predictive power for both models. Performance measures, particularly those related to locomotion ability, explained most of the variance of the LIFE-H 3.1-Brazil daily activity sub-scale. On the other hand, capacity measures, especially walking speed, explained most of the variance of the LIFE-H 3.1-Brazil social role sub-scale. Depressive symptoms were the only variable related to the component of body functions and structure, which showed to be a predictor in both models. These findings suggest that rehabilitation interventions should focus on locomotion ability and walking speed training, when the goal is to increas participation after stroke. Additionally, the presence of depressive symptoms shouldnot be underlooked.